Pengaruh bauran pemasaran terhadap keputusan konsumen menggunakan jasa angkutan bis trayek Pontianak-Sintang kelas executive pada PT. ADAU KAPUAS - Sinhan 01; Hajijah A (Universitas Muhammadiyah Pontianak, 2015)
This study aims to determine the effect of marketing mix consisting of product, price, promotion, place, people, process, physical evidence, the consumer decision to use bus transportation services PT.ADAU KAPUAS route Pontianak-Sintang. The population in this study are all passengers using bus transportation services route Pontianak-Sintang class executive at PT. Adau KAPUAS. While the sample is part of the number and characteristics of being owned by the population. The samples used were asmany as 100 people with sampling techniques. The sampling technique used is incidental sampling is according Sugiono (2003: 65)